2015
DOI: 10.1080/15504263.2015.1025013
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Symptoms, Emotion Dysregulation, and Alcohol-Related Consequences Among College Students With a Trauma History

Abstract: Objective Posttraumatic stress disorder (PTSD), alcohol use, and alcohol-related consequences have been linked to emotion dysregulation. Sex differences exist in both emotion regulation dimensions and alcohol use patterns. This investigation examined facets of emotion dysregulation as potential mediators of the relationship between PTSD symptoms and alcohol-related consequences and whether differences may exist across sexes. Methods Participants included 240 college students with a trauma history who reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 77 publications
5
55
0
Order By: Relevance
“…According to authors of one study, this may have been due to restricted range of alcohol behaviors (Klemanski et al, 2012). The other study found evidence of mediation for the impulse control and emotional clarity facets only when examining solely men (Tripp & McDevitt-Murphy, 2015). Thus, more research examining multi-dimensional aspects of emotion regulation as a mediator of PTSD-alcohol associations is needed, as findings have been mixed and have been unable to parse out the effects of trauma and PTSD in considering these mediated pathways.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to authors of one study, this may have been due to restricted range of alcohol behaviors (Klemanski et al, 2012). The other study found evidence of mediation for the impulse control and emotional clarity facets only when examining solely men (Tripp & McDevitt-Murphy, 2015). Thus, more research examining multi-dimensional aspects of emotion regulation as a mediator of PTSD-alcohol associations is needed, as findings have been mixed and have been unable to parse out the effects of trauma and PTSD in considering these mediated pathways.…”
Section: Introductionmentioning
confidence: 78%
“…Although the mediating role of some specific aspects of emotion regulation have been tested (e.g., non-judgmental acceptance, see Vujanovic, Bonn-Miller, & Marlatt, 2011), in general, studies examining the full, multi-dimensional emotion regulation construct have been sparse and findings have been somewhat mixed. In one of only a handful of such studies, authors found that some facets of emotion regulation (i.e., difficulty with impulse control and goal-directed behavior when upset) mediated the association between PTSD symptoms and alcohol-related consequences in a sample of college students, but assessment of trauma and PTSD were self-report and analyses did not allow for comparisons between trauma exposure only and PTSD (Tripp et al, 2015). Findings from two other studies using military samples did not find emotion regulation to mediate the PTSD-alcohol association (Klemanski, Mennin, Borelli, Morrissey, & Aikins, 2012; Tripp & McDevitt-Murphy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One such example of symptom overlap across those with anxiety and depressive disorders is emotion dysregulation, as evinced by reports of negative biases (Beck & Clark, 1997;Gotlib, Krasnoperova, Yue, & Joormann, 2004) and difficulty in managing negative emotions in ways that are adaptive (Aldao, Nolen-Hoeksema, & Schweizer, 2010;Amstadter, 2008;Fernandez, Jazaieri, & Gross, 2016;Hostinar, Nusslock, & Miller, 2017;Shapero, Abramson, & Alloy, 2016;Tripp, McDevitt-Murphy, Avery, & Bracken, 2015;Tull, Bardeen, DiLillo, Messman-Moore, & Gratz, 2015). A well-studied form of emotion regulation is cognitive reappraisal, an antecedent emotion regulation strategy that occurs prior to or when an emotional experience is unfolding and involves the cognitive transformation (e.g., reinterpretation) of an emotional experience in order to change its emotional meaning (Gross, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, earlier substance use may increase likelihood of later substance dependence (Chen et al, 2009), with these difficulties also playing a role in the emergence of offending behaviour into adulthood (Wiesner et al, 2005). Researchers and clinicians remain divided regarding whether or not substance use is an independent cause of mental health problems and vice versa (Burns, 2013;Mathews et al, 2013;McLaren et al, 2010;Seddon, 2010;Tripp et al, 2015;Wahlstrom et al, 2015) and the extent to which substance use leads to crime also remains in contention (Seddon, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such correlation studies tend to be specific to population, circumstance and measures thus rarely lead to robust interventions (Tripp et al, 2015;Wahlstrom et al, 2015).…”
Section: Introductionmentioning
confidence: 99%